2005
DOI: 10.1007/bf03404031
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Effectiveness of Warning Labels on Cigarette Packages

Abstract: Background: Since 1989 when health warning labels appeared on Canadian cigarette packages, the labels have changed from text only covering less than one quarter of the package to text and graphics covering over half the package. This study examines how Canadians in their 20s feel about the current graphic warning labels and their potential to prevent smoking and encourage quitting.Methods: Participants between 20 and 24 years of age were part of a 10-year cohort study begun when the group was in Grade 6, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 17 publications
3
27
1
Order By: Relevance
“…Studies were published between 1997 and 2005 and were conducted in Australia,46 Canada,47 48 the United States49 and The Netherlands 50. We found no consistent evidence of differential effects on smoking behaviour by education for smoking behaviour46 50 or on smoking attitudes or behaviour by gender 46 48 50.…”
Section: Resultscontrasting
confidence: 60%
“…Studies were published between 1997 and 2005 and were conducted in Australia,46 Canada,47 48 the United States49 and The Netherlands 50. We found no consistent evidence of differential effects on smoking behaviour by education for smoking behaviour46 50 or on smoking attitudes or behaviour by gender 46 48 50.…”
Section: Resultscontrasting
confidence: 60%
“…In our study, the health warning labels increased the curiosity of around 20% of females to be better informed or be helped to stop smoking. Similarly, in a study by Koval et al, female current smokers were more likely to think about quitting smoking 56. Furthermore, males were significantly more affected by the health warnings related to physical fitness ability, particularly shortness of breath.…”
Section: Discussionmentioning
confidence: 76%
“…About 30% of non-smokers in 28 European nations reported that health warnings were effective in preventing them from smoking 65. A Canadian study of PWLs66 found that about 30% of young adults said that they were less likely to start smoking. Similar results have been found in experimental studies 40.…”
Section: Resultsmentioning
confidence: 99%